Respostas

2014-07-14T19:19:42-03:00
A equação x²-6x-2=0 tem duas raízes diferentes, expressas por x¹ e x². Nessas condições, dê o valor de:
a)x¹+x²  b)x¹.x²

x² - 6x - 2 = 0
a = 1
b = - 6
c = - 2
Δ = b² - 4ac
Δ = (-6)² - 4(1)(-2)
Δ = 36 + 8
Δ = 44-------------------------------------------------√44 =2√11
se
Δ > 0
então (baskara)
x = - b - + √Δ/2a
x¹ = -(-6) - √44/2(1)
x¹ = + 6 - 2√11/2

       6 - 2√11    : 2         3 - 1√11
x¹ = -------------        =   ----------- =   3 - √11
           2           : 2              1

e
   
x² = -(-6) + √44/2(1)
x² = + 6 + 2√11/2

         6 + 2√11    : 2           3 + 1√11
x² = ---------------        =     ------------   =     3 + √11
             2           : 2                 1

a)x¹+x²  

  3 - √11  + 3 + √11
 3 + 3 - √11 + √11
      6        + 0          = 6

x¹ + x² = 6
      
 b)x¹.x²

(3 - √11)(3 + √11)
9 + 3√11 - 3√11 + √11√11
9           + 0         +  √11.11
9 + √11² -------------elimina a √ com o (²)
9 + 11 = 20

x¹.x²= 20